Exploring the Potential of Electrospun Polymers for High-Performance Dental Composite: A Mini Review - Sudiyasari, Nadiya; Rahman, Siti Fauziyah (Universitas Indonesia, 2024)
Dental resin composite is the most common material used in dentistry. Resin composite refers to combination of two or more materials that typically consists of matrix polymers, fillers, and a coupling agent. Fillers are essential in composites, as their presence significantly improves the material's hardness. However, beside its excellent mechanical properties, Resin composite also has several limitations, including polymerization shrinkage, a high coefficient of thermal expansion, and low wear resistance. Adding reinforcement materials such as electrospun fiber to composite fillers has shown improvement of its mechanical properties. Electrospun fiber refers to a fiber that produced through electrospinning methods. There are various types polymers used in electrospinning fabrication, such as Poly(methyl methacrylate) (PMMA), Polyacrylonitrile (PAN), Polyether ether ketone (PEEK), Polyvinyl alcohol (PVA), Polycaprolactone (PCL), and Polylactic acid (PLA). The electrospinning method utilizes a high-voltage electrical source applied to these polymer solution. Electrical voltage will initiate the formation of droplets that then elongate to form fibers. Electrospun fibers have versatile applications in dentistry and can be used as a reinforcing agent for dental composite restorations. Therefore, electrospun fibers has a lot of promising potential in dentistry, as they can produce materials with excellent mechanical properties by using a simple and efficient method.